Specific immune response induced by a lactobacillus associated with a pneumococcal antigen in an "in vitro" human cells model - Vintiñi, Elisa Ofelia (2012)
In this work we assessed the immune response induced by combinations of live (LcV) and heat-killed (LcM)Lactobacillus casei CRL 431 as adjuvants associated with pneumococcal protective A protein (PppA) in peripheral blood mononuclear cells (PBMCs). LcV, LcM and their combinations with PppA stimulated T, B and NK cells. Thus, all stimuli increased CD25 expression in T CD3 lymphocytes, highest activation being reached with the combinations of LcV or LcM with an antigen (PppA+LcV, PppA+LcM). Expression of CD19 B cells marker was significantly increased in almost all treatments compared with non-stimulated PBMCs, except for PppA. All treatments increased CD86 expression in the LT population, while in B cells only LPS, PppA+LcV and PppA+LcM increased it. NK cells were significantly increased by LPS (P<0.05), PppA+LcM (P<0.01) and PppA+LcV (P<0.01) compared to non-stimulated PBMCs. PppA+LcV and PppA+LcM increased CD56 expression in both NKT and NK cells, while LcM expanded NKT population. Cytokine pattern analysis showed that LcV and LcM stimulated Th, Th2 and Th17 cytokines and exerted an important adjuvant effect when associated with PppA. Correlation with previous results obtained in animal models when the same experimental vaccine was nasally administered is discussed. Human PBMCs would be useful to evaluate the immune response of mucosal vaccines containing lactic acid bacteria associated with a specific antigen.